Protection to Intangible Indigenous Cultural Expressions under Indian Copyright Act: A Means or an Obstacle: Exploring Copyright Protection for Indigenous Cultural Expressions (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Traditional Cultural expressions form an instinctive part of our lives. Our identity is associated with their existence. It is a symbol of dignity and integrity. It helps in maintaining social stability and communal relationships. Inspires the entire human world to move forward and offer the humanity with its valuable property. But, these valuable undefined belongings of a community are in endangered condition due to modern techniques of copying and reproduction. That has resulted in cultural crises as many traditionalindigenousfolk culture are gradually being obliterated. As their purity, originality, identity and dignity is passing into oblivion. This has been made possible by justifying and protecting the creations based on these expressions under existing copyright regime. Thereby, affecting the economic social and cultural aspects of claimant’s rights for traditional cultural expressions.The researcher in the given paper tends to discuss the possibilities of ‘Copyright laws’, with reference to India, as a means of protection for “intangible folklores” or TCEs. To what extend the current framework of copyright gratifies the claims and concerns of holders of TCEs in the protection of “intangible folklores” against misappropriation and inappropriate use or is there any need to develop a sui-generis system for the protection of TCEs.